2014
DOI: 10.3747/co.21.2051
|View full text |Cite
|
Sign up to set email alerts
|

Aprepitant and Granisetron for the Prophylaxis of Radiotherapy-Induced Nausea and Vomiting after Moderately Emetogenic Radiotherapy for Bone Metastases: A Prospective Pilot Study

Abstract: ConclusionsThe combination of aprepitant and granisetron was safe and efficacious for the prophylaxis of rinv after both single-and multiple-fraction moderately emetogenic radiotherapy for thoracolumbar bone metastases. Our results require confirmation in a larger population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…However, to the best of our knowledge, no investigation in either vomit-competent animals or humans has been conducted to characterize the validity of the two phases of RINV in a dose- and time-dependent fashion. In fact, the duration of acute RINV phase has arbitrarily been defined as the first day of radiotherapy to the first day after radiation exposure, while the second phase is regarded as nausea and vomiting occurring from day 2 up to 10 days posttherapy [ 160 , 161 ]. Vomiting can be initiated by release of emetic mediators when radiation therapy beams is directed toward the: (i) brainstem area or (ii) gastrointestinal portion of the body trunk, where splanchnic/vagal afferents release the aforementioned emetic neurotransmitter involved in CINV [ 162 ].…”
Section: Physiological Mechanisms Of Emesis and Clinical Uses Of Antiemeticsmentioning
confidence: 99%
“…However, to the best of our knowledge, no investigation in either vomit-competent animals or humans has been conducted to characterize the validity of the two phases of RINV in a dose- and time-dependent fashion. In fact, the duration of acute RINV phase has arbitrarily been defined as the first day of radiotherapy to the first day after radiation exposure, while the second phase is regarded as nausea and vomiting occurring from day 2 up to 10 days posttherapy [ 160 , 161 ]. Vomiting can be initiated by release of emetic mediators when radiation therapy beams is directed toward the: (i) brainstem area or (ii) gastrointestinal portion of the body trunk, where splanchnic/vagal afferents release the aforementioned emetic neurotransmitter involved in CINV [ 162 ].…”
Section: Physiological Mechanisms Of Emesis and Clinical Uses Of Antiemeticsmentioning
confidence: 99%
“…More patients on the emetic prophylaxis containing tachykinin NK-1 receptor antagonists reached a complete response [ 25 ]. Dennis et al showed the combination of granisetron and aprepitant being safe and efficacious for the prophylaxis of RINV in single and multiple fraction moderately emetogenic radiotherapy for thoracolumbar bone metastases evaluating only a very small sample size with 19 patients [ 26 ].…”
Section: Prevention and Treatmentmentioning
confidence: 99%
“…[11][12][13] Few reported clinical trials have provided efective prevention or treatment recommendations for RINV. [14][15][16] Concurrent chemotherapy radiotherapy is commonly used for locally advanced head and neck cancers 17 and locally advanced esophageal cancers. 18 Tere are no known prospective phase 3 clinical trials for the prevention of chemotherapy radiotherapy-induced nausea and vomiting for these malignancies.…”
mentioning
confidence: 99%